Some evidence of purchasing power parity - Peter S. Sephton (The Open Economics Journal, 2008)
Empirical support for purchasing power parity is mixed with results dependent on the time frame and countries under examination, the methodology employed, attempts to control for aggregation bias in the data, and whether adjustments are made to account for productivity differences across nations. As a central component of macroeconomic thinking, purchasing power parity is battered and battle-worn. Using methods that allow for breaking means and trends, this research note provides irrefutable evidence in favor of purchasing power parity for a wide range of countries since the late 1800s. The results suggest managers can consider purchasing power parity a long-term anchor around which they can build their strategic plans.
Keywords: 330; real exchange rate; fractional integration; long-memory; purchasing power parity